Diagnosis of pharmaceutical service for the Specialized Component and Special Drug Program in municipalities in the Rio Grande do Sul - Sara M. GALLINA; Tanúbia MENDES; Raqueli A. BITTENCOURT; Júlia W. VIEIRA; Fabíola MISTURINI; Diogo PILGER; Isabela HEINECK (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objectives: Diagnosis of the structure, process, and result of Pharmaceutical Service for the Specialized Component and Special Drug Program carried out in municipal pharmacies, together with the Basic Component, in municipalities in the Rio Grande do Sul. Methods: The research is characterized by a cross-sectional study carried out in 22 public pharmacies in RS cities that dispense drugs from Specialized Component, Special Drug Program and Basic Components. Data collection addressed aspects of structure, processes, and results and was carried out through interviews, document analysis, and direct observation. Data collection took place between January and March 2020, with the aid of the Epicolletc application, which allows the capture of data through text, photos, and video entry forms. Data were extracted, coded, and analyzed using the Excel program (approval opinion in CEP/UFRGS nº 2.437.516). Results: In 81.8% of Pharmacies there is a specific room for the Specialized Component and 36,4% of the pharmacies have Standard Operating Procedures (SOPs). Daily temperature control of thermolabile storage locations occurs in 86.4% of locations. The monitoring record of users, in relation to clinical outcomes, occurs in 18.2% of services. Approximately 50% of the places visited claimed to guarantee the integrality of the treatments. Conclusion: The present study showed good results regarding structure when compared to previous research and PNAUM. In the item processes, it is necessary to advance in order to qualify the service, the follow-up to the patient, so that the results in the patient's health and quality of life are achieved.